Literature Review Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Discovery Learning - -, Fuji Dwi Fahma; Helendra; Fadilah, Muhyiatul; Anggriyani, Ria (Jurnal Biogenerasi, 2024)
This study aims to examine the development of Student Worksheets (LKPD) based on Discovery Learning through a literature review. LKPD based on Discovery Learning is one of the effective learning media to improve critical thinking skills, problem solving, and students' understanding of concepts independently. The method used in this study is a literature review by examining various reference sources related to the development of LKPD, the application of the Discovery Learning model, and its impact on student learning outcomes from the Google scholar database from 2017 to 2023. The results of the review show that the development of LKPD based on Discovery Learning has a positive influence on the learning process, by increasing active participation and deeper understanding of the material. In addition, analysis of various studies shows challenges in implementation, such as time constraints, teacher readiness, and curriculum adaptation. Therefore, training is needed for educators and adjustments to LKPD to make it easier to apply in various classroom conditions. This study is expected to be a reference for the development of LKPD that is more effective and innovative in supporting Discovery Learning-based learning in schools.